Hippocampal-prefrontal theta-gamma coupling during performance of a spatial working memory task - Tamura, Makoto (Nat Commun, 2017)
Cross-frequency coupling supports the organization of brain rhythms and is present during a range of cognitive functions. However, little is known about whether and how long-range cross-frequency coupling across distant brain regions subserves working memory. Here we report that theta–slow gamma coupling between the hippocampus and medial prefrontal cortex (mPFC) is augmented in a genetic mouse model of cognitive dysfunction. This increased cross-frequency coupling is observed specifically when the mice successfully perform a spatial working memory task. In wild-type mice, increasing task difficulty by introducing a long delay or by optogenetically interfering with encoding, also increases theta–gamma coupling during correct trials. Finally, epochs of high hippocampal theta–prefrontal slow gamma coupling are associated with increased synchronization of neurons within the mPFC. These findings suggest that enhancement of theta–slow gamma coupling reflects a compensatory mechanism to maintain spatial working memory performance in the setting of increased difficulty.